(untitled) (Comprehensive Journal of Science, 2026)
The aim of this study to identify the impact of knowledge management on improving employees performance through a field study conducted on technical education institutions in the city of Bani Walid. The study adopted the descriptive analytical approach,and a questionnaire was used as the main tool for data collection from a sample of 30 employees. There are four main dimensions of knowledge management this study examined, namely: knowledge creation, knowledge application, knowledge sharing, and knowledge storage, and measured their impact on improving employees performance. The results revealed a statistically significant relationship between knowledge management and the improvement of employees performance, as knowledge management practices contribute positively to enhancing performance efficiency, promoting creativity,and improving decision making processes within the organization. The results also showed that managements encouragement of employee innovation, support for a culture of knowledge application, strengthening communication and information exchange among employees, and attention to knowledge storage are all factors that lead to improved job performance. The study recommended the necessity of enhancing the implementation of knowledge management within institutions, supporting employees both financially and morally, establishing specialized knowledge management units, and encouraging continuous training and knowledge exchange, in a way that contributes to achieving institutional excellence